Comparison of toxR and tlh based PCR assays for Vibrio parahaemolyticus. (July 2017) - Taiwo, Michael; Baker-Austin, Craig; Powell, Andy; Hodgson, Emily; Natås, Olav B.; Walker, David I.
Abstract: Vibrio parahaemolyticus is a Gram-negative bacterium found in marine and estuarine environments and is globally the leading cause of bacterial seafood-related illness. A real-time PCR assay for V. parahaemolyticus was developed for the marker toxR, with a large-scale and direct comparison of its applicability as a species-specific marker compared to the tlh gene carried out. Assays for tlh and toxR were used for 255 presumptive V. parahaemolyticus strains from our strain library, utilising both real-time ( toxR ) and conventional PCR assays ( tlh ). Of the 255 strains test, 254 results were in concordance; 255 strains were identified as being toxR positive (100%) and 254 strains were tlh positive (99.6%). The single discordant strain (isolate V12/023) was of interest, because it represented a presumptive V. parahaemolyticus strain, isolated from a clinical case. Whole genome sequence analysis and multi locus sequence typing of this single discordant strain was carried out, which unambiguously identified that the isolate was indeed V. parahaemolyticus. Genome analysis identified mismatches in the primer binding sites for the established tlh assay is likely responsible for the assay failing on this particular strain. The identification of false-negative results in strains that are implicated in human infections using the tlh assay and clearly highlights the relevance of the comparison with a toxR assay which showed 100% identification for the V. parahaemolyticus strains tested. Highlights: A new species specific real-time PCR for Vibrio parahaemolyticus was developed. A side-by-side comparison with an established method was conducted. A strain of V. parahaemolyticus was found to be negative for the established method. The same strain was found to be positive for the new method. This strain was further characterised by whole genome sequencing and MLST.